2002
DOI: 10.1177/107327480200900105
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma: Chemotherapy to Biochemotherapy

Abstract: Biochemotherapy remains a promising new treatment for metastatic melanoma. A large Intergroup trial E3695 comparing concurrent biochemotherapy to combination chemotherapy alone is powered to answer important survival questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Response rates on traditional DTIC-based chemotherapy regimens are often low, with percentages below 10% [7]. Recent treatment with BRAF inhibitors or anti-CTLA4 has yielded response rates with a significant improvement in the 1-year survival, but the long-term survival benefits are to be awaited [8,9]. Moreover, these new agents may induce complications, with considerable morbidity and development of other skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Response rates on traditional DTIC-based chemotherapy regimens are often low, with percentages below 10% [7]. Recent treatment with BRAF inhibitors or anti-CTLA4 has yielded response rates with a significant improvement in the 1-year survival, but the long-term survival benefits are to be awaited [8,9]. Moreover, these new agents may induce complications, with considerable morbidity and development of other skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It is ranked as the 5 th most common cancer in men and the 6 th most common cancer in women (Sober et al, 2008). Additionally, the 5-year survival for the metastatic melanoma is still significantly high, when compared to the non-metastatic type (O'Day et al, 2002). This is due, in part, to the relative resistance of metastatic melanoma to chemotherapeutic agents (O'Day et al, 2002).…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, the 5-year survival for the metastatic melanoma is still significantly high, when compared to the non-metastatic type (O'Day et al, 2002). This is due, in part, to the relative resistance of metastatic melanoma to chemotherapeutic agents (O'Day et al, 2002). Thus, it is essential to develop new therapeutic agents targeting unique molecular signaling pathways important for the development of the malignant and invasive neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Among human cancers, melanoma appears to be uniquely suited to the use of this treatment modality, since this tumor tends to be highly immunogenic. 4,32 Intriguingly, an immunodominant epitope of the Melan A/MART-1 antigen is conserved in dogs, 22,34 and as it is in people, its expression may be prognostically significant. 35 The use of the biologic response modifiers IL-2 and interferon a (IFN-a) has been evaluated in various human clinical trials, with objective responses observed in 20-30% of patients.…”
Section: Discussionmentioning
confidence: 99%